The Other-Race-Effect on Audiovisual Speech Integration in Infants: A NIRS Study - Ujiie, Yuta; Kanazawa, So; Yamaguchi, Masami K. (Frontiers in Psychology, 2020)
Previous studies have revealed perceptual narrowing for the own-race-face in face discrimination, but this phenomenon is poorly understood in face and voice integration. We focused on infants’ brain responses to the McGurk effect to examine whether the other-race effect occurs in the activation patterns. In Experiment 1, we conducted fNIRS measurements to find the presence of a mapping of the McGurk effect in Japanese 8- to 9-month-old infants and to examine the difference between the activation patterns in response to own-race-face and other-race-face stimuli. We used two race-face conditions, own-race-face (East Asian) and other-race-face (Caucasian), each of which contained audiovisual-matched and McGurk-type stimuli. While the infants (N = 34) were observing each speech stimulus for each race, we measured cerebral hemoglobin concentrations in bilateral temporal brain regions. The results showed that in the own-race-face condition, audiovisual-matched stimuli induced the activation of the left temporal region, and the McGurk stimuli induced the activation of the bilateral temporal regions. No significant activations were found in the other-race-face condition. These results mean that the McGurk effect occurred only in the own-race-face condition. In Experiment 2, we used a familiarization/novelty preference procedure to confirm that the infants (N = 28) could perceive the McGurk effect in the own-race-face condition but not that of the other-race-face. The behavioral data supported the results of the fNIRS data, implying the presence of narrowing for the own-race face in the McGurk effect. These results suggest that narrowing of the McGurk effect may be involved in the development of relatively high-order processing, such as face-to-face communication with people surrounding the infant. We discuss the hypothesis that perceptual narrowing is a modality-general, pan-sensory process.